Selection of staphylococci strains isolated from a Portuguese traditional fermented/dry sausage for potential use as starter cultures - Carvalho, L. (2013)
In order to evaluate its potential use as starter cultures, 104 isolates of Staphylococcus spp. were obtained from sausages and different sampling environment points in workshops A and B, at southern region of Portugal. PCR amplification was carried out to confirm genus and species allocation. From workshop A, 47 isolates were staphylococci, the majority belonging to the specie S. equorum, while from workshop B, of the 57 isolates identified as staphylococci, most were S. xilosus. The genetic profiles of isolates were further compared using PCR fingerprinting analysis, guiding to the selection of 43 representative strains subsequently characterized for their nitrate reductase, lipolytic and proteolytic activities. Among these strains, 30% revealed proteolytic ability while 42% had lipolytic activity. 65% of the strains reduced nitrate. Subsequently, 10 strains (representatives of different fingerprinting groups) were evaluated for their ability to grow at different temperatures, pH and NaCl concentrations. S. xylosus and S. equorum showed to growth under all the studied conditions being more effective at 15° C, 20° C and pH 5.5 at 20° C, and NaCl concentrations of 10% and 15%; therefore can be guaranteed their application in technological processes with varying temperatures. In workshop A, strains P05-58 S. carnosus and P05-74 S. equorum and, from workshop B, P06-01 and P06-26 S. xylosus presented the most interesting features.